PARTICIPATION OF THE YOUNG GENERATION IN THE PRESERVATION OF THE CULLINARY ART CULTURE OF KUNINGAN'S STICKY RICE TAPE - Widiastuti, Novi; Rakhman, Anita; Hartini, Sri (P2M STKIP Siliwangi, 2019)
This study describes the participation of young generation in the village of Cigugur in preserving the culinary art culture of Kuningan sticky rice tape. Through this research, it is expected that the young generation in the village of Cigugur can obtain knowledge and make a business opportunity from the preservation of the culinary art culture of Kuningan sticky rice tape. The purpose of this study is: To describe the participation of the young generation in the preservation of local culture. This study used a qualitative approach with descriptive methods on the young generation in Cigugur Village, Kuningan Regency. The results in this study concluded that the participation of the young generation in preserving one of the local cultures of Kuningan, namely sticky rice tape is by studying the making of sticky rice tape through a culinary art training program for making the sticky rice tape. Now, the form of participation is abstract participation, that is to say energy and mind. The training activities held by the community involved the community as organizers as well as presenters. The participation of the young generation is energy by taking part in the overall training, and contributing ideas about the innovation of taste and packaging of sticky rice tape to be more attractive to consumers.